Two Strategies Are Proposed According To Active Education And Their On The Effect On The Acquisition Of Mathematical Concepts For Second Grade Students In Mathematics - Jasim Al-Dulaimy, Basim Mahammad; Jabbar Faris, Ilham; Risen Al-Kinan, Hassan Kamil (Opción, 2019)
The weakness of students in their acquisition of the concepts of mathematics and their inability to absorb them, as well as their inability to mathematical topics and ways to solve it for many reasons, and may be one of the reasons for weakness is the teaching methods used in mathematics at various stages and the organization of the method, as the teaching material is often provided in a dry and focused manner On memorization and memorization, it seems like an artificial thing has nothing to do with reality, which makes the student feel difficult to learn. Through the modest experience of researchers in the field of teaching mathematics, they noticed that there are difficulties experi- enced by students in learning mathematics, which reflects negatively on their acquisition of mathematical concepts, and may be one of the reasons is the teaching methods used in which the role of the student receiving information and knowledge only and not involved in The educational process of learning, as evidenced by the questionnaire distributed to (25) mathematics teachers for middle school and from several schools shows that the answer to the first question (Do you adopt modern teaching strategies and methods other than memorization and memorization?) Was 85% of the alternative (k No, as well as the conclusions of several studies, including the study (Janabi, 2018), where the conclusions confirmed that one of the main reasons for poor students’ ac- quisition of mathematical concepts is due to the adoption of traditional teach- ing methods of mathematics teachers and away from the adoption of strate- gies and modern methods that may help improve the ability of students In the acquisition of mathematical concepts.